A new host-targeted antiviral cyclolignan (SAU-22.107) for Dengue Virus infection in cell cultures. Potential action mechanisms based on cell imaging (2023)
ABSTRACT: Dengue virus (DENV) infection is the most arbovirosis in the world. However, medications have not been approved for its treatment. Drug discovery based on the host-targeted antiviral (HTA) constitutes a new promising strategy, considering their high genetic barrier to resistance and the low probability of selecting drug resistance strains. In this study, we have tested fifty-seven podophyllotoxin-related cyclolignans on DENV-2 infected cells and found the most promising compound was S.71. Using cellular and molecular biology experiments, we have discovered that the new lignan altered the distribution of microtubules, induced changes in cell morphology, and caused retraction of the rough endoplasmic reticulum. In addition, the compound alters the viral envelope protein and the double-stranded RNA, while there is a decrease in negative-strand RNA synthesis; especially when the compound was added between 6- and 12-hours post-infection. Altogether, S.71 decreases the viral yield through an HTA-related mechanism of action, possibly altering the DENV genome replication and/or polyprotein translation, through the alteration of microtubule distribution and endoplasmic reticulum deterioration. Finally, pharmacokinetic predictors show that S.71 falls within the standard ranges established for drugs.